Surgical Reconstruction with the Remnant Ligament Improves Joint Position Sense as well as Functional Ankle Instability: A 1-Year Follow-Up Study - Kamizato Iwao; Deie Masataka; Fukuhara Kohei (The Scientific World Journal)
Introduction. Chronic functional instability—characterized by repeated ankle inversion sprains and a subjective sensation of instability—is one of the most common residual disabilities after an inversion sprain. However, whether surgical reconstruction improves sensorimotor control has not been reported to date. The purpose of this study was to assess functional improvement of chronic ankle instability after surgical reconstruction using the remnant ligament. Materials and Methods. We performed 10 cases in the intervention group and 20 healthy individuals as the control group. Before and after surgical reconstruction, we evaluated joint position sense and functional ankle instability by means of a questionnaire. Results and Discussion. There was a statistically significant difference between the control and intervention groups before surgical reconstruction. Three months after surgery in the intervention group, the joint position sense was significantly different from those found preoperatively. Before surgery, the mean score of functional ankle instability in the intervention group was almost twice as low. Three months after surgery, however, the score significantly increased. The results showed that surgical reconstruction using the remnant ligament was effective not only for improving mechanical retensioning but also for ameliorating joint position sense and functional ankle instability.